Cognitive Science, the Explanatory Gap and Kripke Against the Mind-brain Identity Theory - Maja Malec; Olga Markič (Ars & Humanitas, 2025)
Cognitive science, by its inherently interdisciplinary nature, faces the challenge of integration. This paper outlines the challenge and provides a short history of the proposed solutions. Yet another challenge comes from philosophers who believe that the mind is radically different from the body (the mind-body problem), often identifying consciousness as the most recalcitrant aspect of the mind (the problem of consciousness). We begin by examining Saul Kripke’s argument against the possibility of identifying mental states with physical states, as proposed in the mind-brain identity theory, and argue that it is not decisive. We then discuss the difficulty of investigating and explaining subjective experience with the standard scientific methods and conclude with two contemporary approaches that aim to bridge this explanatory gap.